Structural and spectroscopic characterization of a charge-separated uranium benzophenone ketyl radical complex - Lam, Oanh P.; Anthon, Christian; Heinemann, Frank Wilhelm; O'Connor, Jose-Enrique; Meyer, Karsten (Journal of the American Chemical Society, 2008)
The reaction of [((ArO)tacn)U] (1) with 4,4′-di-tert-butylbenzophenone affords a unique isolable U(IV) ketyl radical species [((ArO)tacn)U (OC•Ph)] (2) supported by XRD data, magnetization measurements, and DFT calculations. Isolation and full characterization of the corresponding diphenyl methoxide complex [(( ArO)tacn)U(OCTPh )] (3) is also presented. The one-electron reduction of benzophenone by [((ArO)tacn)U] (4) leads to a purple U(IV) ketyl radical intermediate [((ArO)tacn)U (OC•Ph)] (5). This species is highly reactive, and attempts at isolation were unsuccessful and resulted in methoxide complex [((ArO)tacn)U(OCHPh)] (6) from H abstraction and dinuclear paracoupled complex [((ArO) tacn)U(OCPhPh-CPhO)U(( ArO)tacn)] (7). © 2008 American Chemical Society.